The industrial solvent trichloroethylene induces LRRK2 kinase activity and dopaminergic neurodegeneration in a rat model of Parkinson’s disease - De Miranda, Briana R. (Neurobiol Dis, 2021)
Gene-environment interaction is implicated in the majority of idiopathic Parkinson’s disease (PD) risk, and some of the most widespread environmental contaminants are selectively toxic to dopaminergic neurons. Pesticides have long been connected to PD incidence, however, it has become increasingly apparent that other industrial byproducts likely influence neurodegeneration. For example, organic solvents, which are used in chemical, machining, and dry-cleaning industries, are of growing concern, as decades of solvent use and their effluence into the environment has contaminated much of the world’s groundwater and soil. Like some pesticides, certain organic solvents, such as the chlorinated halocarbon trichloroethylene (TCE), are mitochondrial toxicants, which are collectively implicated in the pathogenesis of dopaminergic neurodegeneration. Recently, we hypothesized a possible gene-environment interaction may occur between environmental mitochondrial toxicants and the protein kinase LRRK2, mutations of which are the most common genetic cause of familial and sporadic PD. In addition, emerging data suggests that elevated wildtype LRRK2 kinase activity also contributes to the pathogenesis of idiopathic PD. To this end, we investigated whether chronic, systemic TCE exposure (200 mg/kg) in aged rats produced wildtype LRRK2 activation and caused nigrostriatal dopaminergic dysfunction. Interestingly, we found that TCE not only induced LRRK2 kinase activity in the brain, but produced a significant dopaminergic lesion in the nigrostriatal tract, elevated oxidative stress, and caused endolysosomal dysfunction and α-synuclein accumulation. Together, these data suggest that TCE-induced LRRK2 kinase activity contributed to the selective toxicity of dopaminergic neurons. We conclude that gene-environment interactions between certain industrial contaminants and LRRK2 likely influence PD risk.